1988
DOI: 10.4067/s0370-41061988000400004
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis en niños

Abstract: Child tuberculosis in south-east SantiagoTwenty two cases of tuberculosis (TB) in children along 1985 at south-east Santiago were retrospectivelly analized. There were 4 cases of extrapulmonary primary locations: 2 renal and 2 mcningeal TB. All four patient had scars of previous BCG vaccination. Thirteen asymptomatic patients were detected at screening procedures for contacts of active TB cases. In 7 of 18 cases with lung TB tubercle bacilli was isolated from sputum or gastric aspirate, In 5 of 17 cases of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Reviste una importancia especial el aspecto nutricional, puesto que los niños desnutridos tienen mayor riesgo de padecer enfermedades contagiosas, así lo muestran nuestros resultados y de algunos estudios, en donde los casos más graves los presentaron niños de menor peso (7,12,13).…”
Section: Revista Medicaunclassified
See 1 more Smart Citation
“…Reviste una importancia especial el aspecto nutricional, puesto que los niños desnutridos tienen mayor riesgo de padecer enfermedades contagiosas, así lo muestran nuestros resultados y de algunos estudios, en donde los casos más graves los presentaron niños de menor peso (7,12,13).…”
Section: Revista Medicaunclassified
“…Se considera que los casos pediátricos son los centinelas de la comunidad, pues sugiere una transmisión reciente por parte de un adulto bacilífero, por eso hacemos hincapié en la necesidad de continuar el estudio de los contactos. Las madres siguen siendo la principal fuente de contagio para los niños, ya que con ellas se establecen los contactos más directos y prolongados (7,12).…”
Section: Revista Medicaunclassified
“…In a 1988 publication, Lewinson et al described that a 28% of the children hospitalized for TB were malnourished, a rate that exceeded 16.5% of the reference population 13 . Probably, it was believed that a child birth from an infected mother conditioned a greater risk of anergy and progressive malnutrition, a hypothesis refuted in the Correa and Zenteno cohort, which with basic statistics showed that there are no differences in the incidence of infectious disease or growth between the group of children of the tuberculous mother and the control group.…”
Section: Commentary On Correa and Zenteno's Articlementioning
confidence: 99%
“…From the group of infants who remained with their mothers at birth for a period of at least 1 month, because they were born at home or because of a lack of quotas at the Hospital, five were excluded from the study, due to their development of the primoinfection during their stay in the establishment. It was recommended to stop the brestfeeding and to separate the child from his/her mother, because the mother is the main source of contagion 13 The indication of separating the child from the bed of his/her mother would have been maintained in some countries until the end of the 20th century 14 . Nevertheless, thanks to the demonstration of the possibility of treatment of pregnant women without risk to the embryos in formation and the effectiveness of prophylaxis in newborns, this practice became obsolete.…”
Section: Commentary On Correa and Zenteno's Articlementioning
confidence: 99%